The Cochrane Database of Systematic Reviews 2003
DOI: 10.1002/14651858.cd004326
|View full text |Cite
|
Sign up to set email alerts
|

Ear drops for the removal of ear wax

Abstract: Evidence of any efficacy of vitamin B12 in improving the cognitive function of people with dementia and low serum B12 levels is insufficient. The two trials of acceptable methodology (Fourniere 1997; Seal 2002) were restricted to a small number of patients with Alzheimer's disease and other types of cognitive impairment. No trials involving people without dementia or using other definitions of vitamin B12 deficiency were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 22 publications
1
44
0
3
Order By: Relevance
“…Additionally, serum B12 should be checked in all patients with (1) history of gastric bypass surgery, partial or total gastrectomy, terminal ileum disease or resection, or pancreatic insufficiency,14,20,33,200 (2) chronic use of levodopa, histamine type-2 (H2) receptor blockers, or protein pump inhibitors (PPIs),22,33,51,54,342345 or (3) findings suggestive of (a) behavioral and psychological symptoms of dementia (BPSD), (b) SCD, including paresthesias, ataxia, or loss of position or vibratory senses, or (c) pernicious anemia (PA), including low hemoglobin (Hgb), elevated mean corpuscular volume (MCV), or corpuscular changes on peripheral smear 62. If such findings are absent, and patients have moderately severe to severe dementia of longer than two years duration, then universal recommendations14 of assessing for and, when found, treating B12 deficiency may not be supported by reliable evidence 13,16,24,26,92,187,326,346–364. H2 receptor blockers and PPIs impair cobalamin absorption; 18,22,33,365,366 their use is associated with supplemental B12 initiation 367.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, serum B12 should be checked in all patients with (1) history of gastric bypass surgery, partial or total gastrectomy, terminal ileum disease or resection, or pancreatic insufficiency,14,20,33,200 (2) chronic use of levodopa, histamine type-2 (H2) receptor blockers, or protein pump inhibitors (PPIs),22,33,51,54,342345 or (3) findings suggestive of (a) behavioral and psychological symptoms of dementia (BPSD), (b) SCD, including paresthesias, ataxia, or loss of position or vibratory senses, or (c) pernicious anemia (PA), including low hemoglobin (Hgb), elevated mean corpuscular volume (MCV), or corpuscular changes on peripheral smear 62. If such findings are absent, and patients have moderately severe to severe dementia of longer than two years duration, then universal recommendations14 of assessing for and, when found, treating B12 deficiency may not be supported by reliable evidence 13,16,24,26,92,187,326,346–364. H2 receptor blockers and PPIs impair cobalamin absorption; 18,22,33,365,366 their use is associated with supplemental B12 initiation 367.…”
Section: Discussionmentioning
confidence: 99%
“…[48] found that vitamin B12 treatment improves cognitive impairment, but does not reverse dementia. Although evidence of vitamin B12 efficacy in improving the cognitive function of people with dementia and B12 serum concentrations is insufficient [49], it is advisable to screen for vitamin B12 in all patients with cognitive impairment [23]. Recently, folic acid and vitamin B supplementation (B12, B6) has been found to slow the atrophy of brain regions that are associated with cognitive decline [50].…”
Section: The Multifaceted Clinical Presentation Of Cobalamin Deficmentioning
confidence: 99%
“…Among healthy, older adults, there was no consistent evidence that folic acid supplementation with or without vitamin B12 improved cognitive function. A separate Cochrane database review conducted by Malouf and Sastre (41) reported similar findings in an examination of the effects of B12 on cognition, specifically. Three trials were included, all of which examined this association among individuals with cognitive impairment and low levels of serum B12.…”
Section: Dietary Components and Neurocognitionmentioning
confidence: 54%